Tracheoesophageal puncture and quality of life after total laryngectomy: A systematic review and meta‐analysis - Raika Bourmand; Sofia E. Olsson; Arman Fijany (Laryngoscope Investigative Otolaryngology)
Abstract Objective Total laryngectomy (TL) is a standard induction treatment for laryngeal cancer. Patients have shown decreased quality of life (QOL) following laryngectomy potentially due to its impact on communication. This study is a systematic review of the effects of TEP on QOL in TL patients. Methods Data was extracted from PubMed, Ovid Medline, and Web of Science. A systematic review of literature assessing QOL after TEP within the last decade was conducted using PRISMA methodology. The initial search yielded 71 publications filtered to 15 after removing duplicates, non‐English publications, and title screening. Two researchers independently reviewed abstracts, and 11 articles were retained. After a full article review, 6 examined QOL in TEP patients. Results The studies concluded that post‐TL, patients with TEP experienced improved QOL than before the procedure or non‐TEP alternatives for speech. The collective sample size yielded 253 patients. Meta‐analysis demonstrated significant improvement in QOL described by the University of Washington—Quality of Life Index (p < .0001) and insignificant improvement defined by the Voice Handicap Index (p = .07). Several additional indices were included in the articles, all of which indicated improved QOL in TL patients post‐TEP. These scales could not undergo meta‐analysis due to their presence in only 1 study each. Conclusion TEP is a valuable intervention in improving patient QOL and satisfaction following TL. There is no standardized tool for describing QOL in TL patients, so the authors recommend tools be chosen based on the specific aspects of QOL they represent. Level of evidence 2a.